EXPLORATION OF ETHNOMATHEMATICS CONCEPTS IN THE PROCESS OF MAKING BALA SUJI AS A CONTEXTUAL LEARNING RESOURCE - Audya Meilani; Andi Aras; Buhaera Buhaera; Claver Nzobonimpa (EDU-MAT: Jurnal Pendidikan Matematika, 2026)
This study aims to identify and analyze mathematical concepts embedded in the form and function of Bala Suji, a traditional craft of the Pattinjo community in Pinrang Regency. Employing a qualitative approach with ethnographic methods, data were collected through participatory observation, in-depth interviews, and documentation in Kampung Kappe, a village that actively preserves the making of Bala Suji. The findings reveal that Bala Suji embodies various mathematical concepts, including plane and solid geometry (sulapa appa), arithmetic sequences, geometric transformations (reflection, rotation, translation, dilation), and linear equations in two variables. These concepts are applied intuitively by the community through daily cultural practices without formal mathematical terminology. This research affirms that Bala Suji holds not only symbolic and aesthetic value but also potential as a contextual and meaningful learning medium for mathematics. This study contributes to mathematics education by providing a concrete example of integrating local cultural practices into formal mathematics learning and serves as a reference for developing ethnomathematics-based learning resources that enhance conceptual understanding while fostering students cultural awareness. Keywords: Ethnomathematics, Bala Suji, Contextual Learning Resource